2020
DOI: 10.1097/gox.0000000000003285
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Mandible Reconstruction: Controversies and Considerations

Abstract: Summary Mandibular reconstruction in pediatric patients has some unique considerations. The method of reconstruction has to factor in the growth potential of the neo-mandible, the native mandible, and the donor site. The condyle is considered the main growth center of the mandible. Current literature indicates that fibula, iliac crest, and scapula osseous flaps do not have the ability to grow. Costochondral grafts exhibit growth because of the costal cartilage component, although the growth is unpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 95 publications
(18 reference statements)
0
26
0
3
Order By: Relevance
“…For critical size defects that also include soft tissue deficiencies and/or cases that require significant reconstruction of the jawbone, 3D-VSP supported microsurgical reconstruction is indicated. During the last 20 years, craniomaxillofacial surgery has begun to undertake reconstructive treatment of post ablative and posttraumatic defects as well as congenital or acquired deformations in adults, adolescents and children [ 21 , 22 , 23 ]. Prior to dental implant treatment, cleft maxilla requires reconstruction of both hard and soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For critical size defects that also include soft tissue deficiencies and/or cases that require significant reconstruction of the jawbone, 3D-VSP supported microsurgical reconstruction is indicated. During the last 20 years, craniomaxillofacial surgery has begun to undertake reconstructive treatment of post ablative and posttraumatic defects as well as congenital or acquired deformations in adults, adolescents and children [ 21 , 22 , 23 ]. Prior to dental implant treatment, cleft maxilla requires reconstruction of both hard and soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This is of particular concern in young children who are still growing, requiring the restoration of functionality and facial esthetics while not restricting growth. 12 Here, we report the successful immediate reconstruction of a large segmental mandibular defect using a viable cellular bone allograft, ViviGen Formable (VF-CBA), in a pediatric patient following JAOF resection. By providing all 3 essential bone remodeling properties, VF-CBA facilitated fusion at the defect site.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric mandibular reconstruction is typically accomplished using autogenous bone grafts, commonly taken from the iliac crest or fibula. 12 However, autograft harvesting in a growing child is not without potential complications. These include the typical complications associated with donor-site harvest, such as pain and infection, as well as increased operative time due to the complexity of the procedure and, potentially, increased length of hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Furthermore, with proper periosteal repair, the ribs frequently regenerate within 3-6 months, with studies reporting complete regeneration in 44% to 98% of children. 23,24 Long-term chest deformities secondary to rib harvesting have been studied in patients who underwent microtia repair. In one study of 18 pediatric patients, local rib deformities identified via X-ray or CT ranged from 20% to 63.6%, and presented most commonly as a small groove overlaying the operative site 25 ; however, scoliosis secondary to costal cartilage harvest has been considered rare.…”
Section: Discussionmentioning
confidence: 99%